Effectiveness of the online mindset intervention 'The Growth Factory' for adolescents with intellectual disabilities. Issue 1 (4th October 2021) - Verberg, Fenneke; Helmond, Petra; Otten, Roy; Overbeek, Geertjan
Abstract: Background: This study examines participant satisfaction and effectiveness of the online mindset intervention 'The Growth Factory' (TGF) for youth with intellectual disabilities using a randomised controlled trial design. Method: Youth with mild to borderline intellectual disabilities ( N  = 119; 12–23 years) were randomly assigned to TGF ( n  = 60) or control group ( n  = 59). Primary outcome measures were mindsets and perseverance. Secondary outcomes were empowerment, mental health problems, self‐esteem, treatment motivation, therapeutic alliance and challenge seeking. Measurements were conducted at pre‐test, post‐test and at 3 and 6 months follow‐up. Results: TGF had positive effects on perseverance, mental health problems, self‐esteem and therapeutic alliance at post‐test. TGF had follow‐up effects on mental health problems (3 months), mindset of intelligence (3 and 6 months) and mindset of emotion and behaviour (6 months). Conclusions: TGF offers a promising add‐on intervention complementing usual care programmes accelerating improvements in mindsets and mental health in youth with intellectual disabilities.